Financial Literacy and Women Empowerment in Chitwan - Chhetri, Ashmita Dahal (Saptagandaki Journal, 2024)
In this study, the relationship between Financial Literacy and Women's Empowerment is investigated. In order to investigate women's empowerment with age and education serving as moderating variables, the scholar used Financial Literacy (Financial Knowledge, Financial Skill, Financial Behaviour, Financial Attitude, and Financial Awareness) as independent variables. 385 samples were taken using the purposive sampling technique, and data were gathered from individuals in the 18–44 age range using a structured questionnaire survey. SPSS, a statistical analysis program, was used to examine the data. Descriptive analysis and inferential analysis for association and proposition testing are the proper statistical techniques used in research. The results of the study demonstrate a negative and substantial relationship between women's empowerment and financial knowledge and abilities. Additionally, there is a strong and positive correlation between women's employment and financial conduct, attitude, and awareness. Moreover, there is a strong and positive correlation between moderating age and education variables. The research findings establish the critical role that financial literacy plays in promoting gender equality and raising the socioeconomic standing of women.